2006
DOI: 10.4319/lom.2006.4.448
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effective shore level as a method of characterizing intertidal wave exposure regimes

Abstract: Wave splash modifies the duration and timing of aerial exposure of intertidal organisms, influencing patterns of vertical zonation, thermal stress, and the consequences of climate change. Harley and Helmuth (Limnol. Oceanogr. 48:1498-1508) described a method for measuring effective shore level (ESL), a metric that combines the influence of wave splash and tidal regime on patterns of emersion and immersion. They identified immersion events as sharp drops in temperature recorded by submersible dataloggers and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Although water temperatures tend to follow a latitudinal cline, the body temperatures of intertidal species when measured at low tide do not always follow a similar pattern. Thermal stress during low tide is determined by a complex interaction involving factors such as timing of low tide, terrestrial climate, and wave splash, all of which fluctuate along a coastline (Helmuth et al, 2002(Helmuth et al, , 2006Gilman et al, 2006). Thus, some northern sites with cool water temperatures may experience warmer low tide body temperatures than southern intertidal sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although water temperatures tend to follow a latitudinal cline, the body temperatures of intertidal species when measured at low tide do not always follow a similar pattern. Thermal stress during low tide is determined by a complex interaction involving factors such as timing of low tide, terrestrial climate, and wave splash, all of which fluctuate along a coastline (Helmuth et al, 2002(Helmuth et al, , 2006Gilman et al, 2006). Thus, some northern sites with cool water temperatures may experience warmer low tide body temperatures than southern intertidal sites.…”
Section: Discussionmentioning
confidence: 99%
“…For each study site, observed tidal height data were obtained from the nearest National Oceanic and Atmospheric Administration (NOAA) Center for Operational Oceanographic Products and Services observing station ( ). The effect of wave splash was estimated using metrics of significant wave height and shore slope data presented by Gilman et al . (2006a) .…”
Section: Methodsmentioning
confidence: 99%
“…Loggers, like settlement tiles, were placed at 0 m MLLW. For each site, we processed logger data as daily mean values of air and water temperatures using the SiteParser program (Gilman et al 2006). We calculated daily mean salinity values for each site using data from nearby continuous water-quality monitoring stations that were maintained by the US Geological Survey (USGS 2015) and the SF Bay NERR (NERR 2015), and compared these daily means with measurements that were taken during biweekly or monthly site visits using a YSI-85 multimeter (YSI, Yellow Springs, Ohio; Online Resource 1).…”
Section: Environmental Measurements and Data Preparationmentioning
confidence: 99%